Masticatory Ability for a Single Implant Mandibular Overdenture Retained by Two Different Attachments: A Randomized Controlled Trial - Marwa Abdel AaL; Amr Naguib; Ahmed Salah; Karim Foda; Nora Sheta; Nouran Abdel Nabi (International Journal of Dentistry)
Objective. The aim of this randomized clinical trial was to compare the masticatory ability subjectively between ball and Cendres+Métaux Locator (CM-LOC) attachment for a single implant retained mandibular overdenture throughout a 24-month follow-up period. Materials and Methods. Eighty completely edentulous patients were recruited. All patients received new complete dentures, and masticatory ability was recorded using a questionnaire (baseline record). All patients received a single implant in the midline of the completely edentulous mandible. After 3-month healing period, patients were randomized using sealed envelopes into two groups: ball or CM-LOC attachment. The same masticatory ability questionnaire was used to record masticatory ability for both groups after 2 weeks of pickup and 3-, 6-, 9-, 12-, and 24-month follow-up. Comparison between the study groups was done using Mann–Whitney U test for independent samples. Two-sided P values less than 0.05 were considered statistically significant. Results. The mean masticatory scores improved for both attachments, with no statistically significant difference between them throughout the 24-month follow-up. The CM-LOC attachment group showed a greater improvement change in masticatory ability after 6- and 12-month follow-up (−12.47 ± 12.006, −11.46 ± 14.625; P=0.826), while the ball attachment group showed a slight improvement after the 24-month follow-up (−11.72 ± 12.368, −10.88 ± 11.963; P=0.778). Conclusion. Single implant retained mandibular overdenture improved masticatory ability subjectively with no significant difference between both attachments used although the ball attachment showed better masticatory ability scores after 24-month follow-up.